Pengaruh Hard Skills, Soft Skills dan Mediasi Budaya Sekolah Terhadap Kapabilitas Inovasi Guru di Jawa Barat - Masduki Asbari; Agus Purwanto; Laksmi Mayesti Wijayanti; Choi Chi Hyun; Sekundina Williana Kusumaningsih; Evy Yanthy; Firdaus Putra; Winanti Winanti; Donna Imelda; Rudy Pramono; Innocentius Bernarto (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This study aims to measure the effect of hard skills and soft skills on the innovation ability of the teachers in West Java which are mediated by organizational culture. The method used in this research is quantitative method. Data collection is done by simple random sampling via electronic to the teacher population in West Java. The results of the returned and valid questionnaire are 667 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study concluded that hard skills and soft skills have a positive and significant effect on teacher innovation ability, both directly and indirectly through mediating organizational culture. This new research proposes a model to build innovation capabilities of the teachers among teachers in West Java through enhancing hard skills and soft skills with organizational culture as a mediator. This research can pave the way to increase teacher readiness in the face of the education 4.0.